PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DENGAN PROFITABILITAS DAN OPINI AUDIT SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Sintia Maramis; Ria Nelly Sari; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aimed to examine the impact of good corporate governance, profitability, and audit opinion against the timeliness of financial reporting. The population of this research arebanking companies that listed on Indonesian Stock Exchange during 2012-2016. The sample used in this research determined by purposive sampling method, and totally amounted 29 companies that match to the criteria that have been set. The analysis method assisted with SPSS Windows Ver 22. Analysis technique used is the LogisticRegression Analysisby using Moderated Regression Analysis. Based on the analysis concluded that good corporate governance has no effecton the timeliness of financial reporting, profitability is able to moderate the influence of good corporate governance on the timeliness of financial reporting, and audit opinion is not able to moderate the influence of good corporate governance on the timeliness of financial reporting.Keywords : The Timeliness of Financial Reporting, Good Corporate Governance, Profitability, Audit Opinion.